The Role of Autologous Stem Cell Transplantation in the Treatment of Diffuse Large B-cell Lymphoma in the Era of CAR-T Cell Therapy - Lazaros J. Lekakis; Craig H. Moskowitz (HemaSphere, 2019)
Abstract. For many years now and based on the results of the PARMA trial, relapsed Diffuse Large B-cell Lymphoma (DLBCL) is treated with salvage combination cytotoxic chemotherapy (most often platinum-based) followed by high dose myeloablative chemotherapy and autologous stem cell transplantation (auto-HCT). This approach has resulted in long-term disease free survival in about half of the patients. With the incorporation of rituximab in the upfront treatment (RCHOP), more patients with DLBCL are cured but there has been a signal of inferior outcomes with auto-HCT if DLBCL relapses. Nevertheless, a careful review of the literature still shows very good outcomes with auto-HCT for DLBCL with complete remission to salvage chemotherapy. For those who do not respond well to classic salvage other approaches are reviewed here including chimeric antigen receptor (CAR) T-cell therapy and treatment with antibody-drug conjugates (ADCs) as well as bispecific T-cell engagers (BiTEs). The outcome of auto-HCT after successful treatment with ADCs or BITEs is unknown. It is also unknown if CAR-T cell therapy should be reserved for those who have failed 2 lines of chemotherapy or it should be moved earlier. Finally, we review here the effects of Myc and bcl2 amplifications or translocations to the outcome of the auto-HCT. Some attempts to improve the salvage or conditioning regimens are mentioned. We also discuss the role of allogeneic stem cell transplantation (allo-HCT) in the paradigm of treatment for relapsed DLBCL.